In‐Plane Energy Absorption Properties of Novel Curved‐Ligaments Auxetic Cellular Structures with Dual‐Platform Performance - Liu, Xu; Liu, Hai‐Tao; Wang, Shun (physica status solidi (b), 2025)
To improve the energy absorption capacity of honeycomb, four novel curved‐ligaments auxetic cellular structures (CLACS‐i [i = 1, 2, 3, 4]) based on the Diabolo‐shaped honeycomb (DSH) are introduced in this article. In the simulation results, it is demonstrated that the energy absorption performance of CLACS‐i (i = 1, 2, 3, 4) surpasses that of DSH under low‐, medium‐, and high‐velocity impacts. However, the negative Poisson's ratio effect of novel structures is inferior to that of DSH. With the increase in impact velocity, the inertial effect of the structure is enhanced, and the deformation mode of the structure changes from global deformation to local deformation. Furthermore, different impact velocities and geometric parameters also affect the energy absorption capacity of the structures. Platform stress and specific energy absorption (SEA) of CLACS‐i (i = 1, 2, 3, 4) increase with the increase of velocity. Under medium‐velocity impact loading, the platform stress and SEA of CLACS‐i (i = 1, 2, 3, 4) increase as the geometric parameter θ decreases and the wall thickness t increases. In this study, a reference is provided for the optimal design and application of honeycomb energy‐absorbing components. To enhance energy absorption of the honeycomb, four novel curved‐ligaments auxetic cellular structures (CLACS‐i [i = 1, 2, 3, 4]) are designed. The plateau stress and specific energy absorption of CLACS‐i (i = 1, 2, 3, 4) are investigated by using the finite‐element method.